Better to have ability to discover Ability” – The effect of teacher self-efficacy on job satisfaction: implications for best practices - Kengatharan, N. (My University, 2020)
Drawing on social cognitive theory and theory of planned behaviours, the present study investigates the relationship between teacher self-efficacy and teacher job satisfaction. Using a self-reported questionnaire, data were gleaned from randomly chosen 698 teachers working in state schools in Sri Lanka. Strongly based on the ontological and epistemological assumptions, a survey strategy with the hypothetic-deductive approach was adopted. At the outset, fundamental statistical assumptions and common method variance were examined. Results reveal that three components of teacher self-efficacy, that is, adapting education to individual students’ needs, motivating students and keeping discipline, significantly accounted for much variance in teacher job satisfaction, nonetheless, other three components, namely, instruction, cooperating with colleagues and parents, and coping with changes and challenges, were not the significant contributors to teacher job satisfaction. The study has pushed back the frontiers of educational literature and proffered insightful practical implications that are discussed at the end of the paper.
Keywords: Schools; Social Cognitive Theory; Sri Lanka; Teacher Job Satisfaction; Theory of Planned Behaviors; Teacher Self-efficacy